Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting